(3eQGJH GdQDjG hfRhd GdbQBfs ((3CMeO Hf Ydi GdcQcOjfi GdgePGfi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO EYdeG QMece Gddg hQRbce ef GdWjHGJ hCYGfce Ydi JQc GdefcQGJ Cf GdfHi Ydjg GdUdGI hGdSde QCi QH GdYRg ai QeVGf s
(3BNQgG (B:s
(3hCNQL ef fgGjI GdfhQ GdQhM HGdcJGH hGdejRGf hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi NGJe GdfHjjf hYdi Bdg CLeYjf Je BNQ GdMO GdaGQb Hjf GdWjH hGdNHjK s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdbQGAGJ hGdJLhjOs